Child labour and effects of the economic climate on the rights of a child in contemporary Nigeria (1998)
A child is the resource pool from which the future generation is predicated . Many countries are now concerned about the child especially in the area of her right. Child labour was one of the first and most important items targeted for international cooperation. Work is not necessarily detrimental, however it should not be hazardous and exploitative. Certain mechanism influence child survival and development. The gloomy picture presented by the economic climate in Nigeria has made child labour a dominant and problematic area in Nigeria. This in effect has affected the right of the child.